Hematometra and cystic endometrial hyperplasia in a bitch: a case description - Sánchez R., Alfonso (2015)
The case of a 4.5 years old Bullmastiff bitch presented to the clinic with prolonged haemorragic vaginal discharge is described. A systemic involvement was not observed in the gynecological examination, the anestrus status was determined by vaginal cytology and measurement of the progesterone level in plasma (<1 ng/ml), and the presence of uterine content and increased uterine size was confirmed by ultrasonography. Besides, a mild regenerative anemia was determined. Based on a history of irregular estrous cycles an ovariohysterectomy was performed as treatment. In the evaluation of the uterus was observed the presence of blood in the uterine lumen and cysts in the mucosa, what led to the diagnosis of hematometra concomitant with cystic endometrial hyperplasia.